Weeds associated with pasture systems in the low zone of the department of Quindio (Revista de Investigaciones Universidad del Quindío, 2012)
We characterized the weed flora associated with pasture systems in the department of Quindío-Colombia (950m to 1100m), we also identified potential uses of the weed flora associated with thise types of systems. There were reported 80 species, grouped in 70 genera and 36 families; the families with the greatest number of species were Asteraceae with 13 species, Leguminosae with 10, Cyperaceae,with 7especies, Solanaceae with 5, Verbenaceae with 4 species followed by Lamiaceae and Euphorbiaceae with 3 species each one. As for the genera with the greatest number of species in their order are: Cyperus with 4 species, Solanum with 3 species, Solidago, Desmodium, Lantana, Hyptis and Euphorbia with 2 species respectively. Within the spe-cies uses reported by the residents of farms dedicated to cattle in the warm zone of Quindío, we found the fo-llowing: Beekeeping 37% Medical 16%, Hospedería 14%, nitrogen-fixing N. 8% Toxica 6%, Feed 4%, others 15%. However; the farms owners involved in livestock production in this hot area of Quindío, are included within their traditional pasture practices the management of weedkillers spraying, ignoring the potential use of weeds that grown together with their pasture systems.
Keywords: weed flora; pasture system; warm zone; livestock